Analysis of the Impact of Underage Marriage on Divorce in Baubau City - Amrun Kahar; Muhammad Hisyam Faturrahman (AIQU: Journal Multidiscipliner of Science, 2025)
This study aims to analyze the impact of underage marriage on the divorce rate in Baubau City using a normative-empirical legal approach. Early marriage remains a prevalent issue in various regions, including Baubau, and is often linked to a high rate of divorce. The findings reveal a significant correlation between underage marriages and divorce, both in terms of frequency and the resulting social consequences. The primary contributing factors include premarital pregnancy, premarital sexual relations, peer pressure, and cultural or societal norms. The lack of mental and emotional maturity among young couples is a major trigger for disharmony and instability in these hastily formed marriages. Data were collected through documentation from the Office of Religious Affairs (KUA) and interviews with relevant stakeholders. Based on the results, the study recommends the active involvement of parents in supervising and educating their children, with a strong emphasis on moral and religious education from an early age. Additionally, the introduction of comprehensive sex education for adolescents is deemed essential. Government agencies, religious institutions, and educational bodies must work collaboratively to address the issue through public awareness, preventive education, and strict regulatory measures. These efforts are expected to significantly reduce the incidence and impact of early marriage, fostering a healthier, more responsible young generation.